MicroRNA-dependent regulation of biomechanical genes establishes tissue stiffness homeostasis - Moro, Albertomaria; Driscoll, Tristan P.; Boraas, Liana C.; Armero, William; Kasper, Dionna M.; Baeyens, Nicolas; Jouy, Charlene; Mallikarjun, Venkatesh; Swift, Joe; Ahn, Sang Joon; Lee, Donghoon; Zhang, Jing; et al. (Nature cell biology, 2019)
Vertebrate tissues exhibit mechanical homeostasis, showing stable stiffness and tension over time and recovery after changes in mechanical stress. However, the regulatory pathways that mediate these effects are unknown. A comprehensive identification of Argonaute 2-associated microRNAs and mRNAs in endothelial cells identified a network of 122 microRNA families that target 73 mRNAs encoding cytoskeletal, contractile, adhesive and extracellular matrix (CAM) proteins. The level of these microRNAs increased in cells plated on stiff versus soft substrates, consistent with homeostasis, and suppressed targets via microRNA recognition elements within the 3′ untranslated regions of CAM mRNAs. Inhibition of DROSHA or Argonaute 2, or disruption of microRNA recognition elements within individual target mRNAs, such as connective tissue growth factor, induced hyper-adhesive, hyper-contractile phenotypes in endothelial and fibroblast cells in vitro, and increased tissue stiffness, contractility and extracellular matrix deposition in the zebrafish fin fold in vivo. Thus, a network of microRNAs buffers CAM expression to mediate tissue mechanical homeostasis. Moro et al. discover an Argonaute 2 (Ago2)-dependent miRNA network that, in response to substrate stiffness, regulates genes involved in tissue mechanics, and show that Ago2 restrains stiffness and contributes to regeneration in the zebrafish fin fold.